2000
DOI: 10.1115/1.1354142
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Secondary Flow Losses in Turbine Cascades by Leading Edge Modifications at the Endwall

Abstract: Experimental results are presented which show the influence on the secondary flow and its losses by a profile modification of the leading edge very close to the endwall. The investigation was carried out with a well-known turbine profile that originally was developed for highly loaded low pressure turbines. The tests were done in a low speed cascade wind tunnel. The geometrical modification was achieved by a local thickness increase; a leading edge endwall bulb. It was expected that this would intensify the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 2 publications
1
27
0
Order By: Relevance
“…SL2F produces larger losses than SL2P from about 12% to 35% span, and the midspan losses increase by about 10% for both cases. The pitch-averaged loss trends in the current data sets are similar to the results of Sauer et al (2001), who investigated the effects of endwall leading edge bulbs on secondary flows; in their study, the secondary loss reduction was mainly attributed to the intensification of the suction-side leg of the horseshoe vortex, resulting in a weaker passage vortex.…”
Section: Downstream Flow Field Measurements At 14c Xsupporting
confidence: 83%
See 1 more Smart Citation
“…SL2F produces larger losses than SL2P from about 12% to 35% span, and the midspan losses increase by about 10% for both cases. The pitch-averaged loss trends in the current data sets are similar to the results of Sauer et al (2001), who investigated the effects of endwall leading edge bulbs on secondary flows; in their study, the secondary loss reduction was mainly attributed to the intensification of the suction-side leg of the horseshoe vortex, resulting in a weaker passage vortex.…”
Section: Downstream Flow Field Measurements At 14c Xsupporting
confidence: 83%
“…The application of leading edge bulbs to the T106 airfoil ( Figure 2.4) was examined by Sauer et al (2001). The resulting configurations are labelled T106/1 and T106/2 in As mentioned, the modification of the airfoil pressure-surface profile in the present study is mainly aimed at reducing the secondary losses.…”
Section: Airfoil Pressure Surface Modificationmentioning
confidence: 96%
“…Some authors have modified the leading edge region of the endwall to influence the formation of the horseshoe vortex. Sauer et al (2001) tested four leading edge bulb designs applied to the T106 airfoil in a linear cascade. They found that the bulb increased the strength of the suction-side leg of the horseshoe vortex (V s h), which counter-rotates relative to the passage vortex.…”
Section: Leading Edge Modificationsmentioning
confidence: 99%
“…Han and Goldstein [24] used fillet geometry around the blade leading edge, which removes the horseshoe vortex and reduces the heat transfer near the leading edge. Sauer and Wolf [25] employed a bulb geometry onto an inlet guide vane. The bulb design strengthens counter vortex, which counter-acts the passage vortex.…”
Section: Introductionmentioning
confidence: 99%